PENGARUH KEPEMIMPINAN TRANSFORMASIONAL TERHADAP DISIPLIN KERJA GURU DI SMA NEGERI SE-KOTA BUKITTINGGI - Rahmiyana Febriana, Dwi; Tia Ayu Ningrum; Nellitawati; Enceria Damanik (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study is motivated by the importance of transformational leadership exercised by school principals in enhancing teachers’ work discipline. The purpose of this study is to examine the influence of principals’ transformational leadership on teachers’ work discipline in public senior high schools throughout Bukittinggi City. This research employs a quantitative correlational design. The population consisted of 248 teachers from public senior high schools in Bukittinggi City, with a sample of 153 respondents selected using the Stratified Proportional Random Sampling technique. Data were collected through a Likert-scale questionnaire that had been tested for validity and reliability. The data were analyzed using simple linear regression, supported by the t-test and the coefficient of determination (R²). The findings indicate that teachers’ work discipline is categorized as very good, with an achievement level of 96.4%, while principals’ transformational leadership is categorized as good, with an achievement level of 94.95%. The results of the analysis show that the principal's transformational leadership has a positive influence on teacher work discipline in public senior high schools in Bukittinggi City with a contribution of 3.3%, while 96.7% is influenced by other factors outside the research. Therefore, the higher the level of transformational leadership demonstrated by school principals, the better the teachers’ work discipline. Based on the research results, school principals are advised to continue strengthening transformational leadership through role models, providing motivation, intellectual stimulation, and individual attention to teachers so that teacher work discipline can continue to improve.